2007
DOI: 10.1007/s00251-006-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CTL epitopes in hepatitis C virus by a genome-wide computational scanning and a rational design of peptide vaccine

Abstract: Developing a peptide-based vaccine for the highly variable hepatitis C virus (HCV) remains a challenging task. Variant viruses not only escape antigen presentation but also persist in a patient as quasi-species. Such variants are often antagonistic to the responding T cell repertoire. To overcome these problems, we herein propose a cocktail vaccine consisting of a few epitope peptides, which make it possible to outpace the emergence of variant viruses. To design such a vaccine, we developed a way to identify H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…4). All but H57A mutation of NS3 examined in this study are located outside the human CD4 and CD8 epitopes reported so far, with the H57A mutation being located at the C-terminal edge of an epitope [7], [8], [9], [11]. Therefore, these findings suggest that a single mutation in the protease and NTPase/RNA helicase domains would not interfere with immunogenicity of NS3 as a whole in mice and human.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…4). All but H57A mutation of NS3 examined in this study are located outside the human CD4 and CD8 epitopes reported so far, with the H57A mutation being located at the C-terminal edge of an epitope [7], [8], [9], [11]. Therefore, these findings suggest that a single mutation in the protease and NTPase/RNA helicase domains would not interfere with immunogenicity of NS3 as a whole in mice and human.…”
Section: Discussionsupporting
confidence: 47%
“…NS3 is known to carry a variety of CD4 + and CD8 + T cell epitopes to induce strong HCV-specific T cell responses, which are correlated with viral clearance and resolution of acute HCV infection [7], [8], [9], [10], [11]. Also, the HCV core protein is known to carry a variety of CD4 + and CD8 + epitopes [7], [8], [9], [12], [13], [14]. From the antigenic point of view, therefore, NS3 and the core protein would be attractive candidates to be used for therapeutic vaccines that elicit T cell-mediated immune responses against HCV.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting-edge technologies and screening strategies have been developed recently to mine genomic sequence information for state-of-the-art rational vaccine design (40). However, the large size of the HSV-1 genome and the low frequency of HSV-specific CD8 + T cells have hampered genome-wide identification of protective HSV-1 CD8 + T cell epitopes and characterization of the full repertoire of CD8 + T cells that are associated with the “natural protective immunity" seen in ASYMP individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Betts and colleagues have described the CD107 a/b assay as an alternative cytotoxicity assay that is able to address some of the shortcomings of the 51 Cr release assay. The intracellular assay to detect IFN-γ and CD107 a/b in response to in vitro peptide stimulations was performed as described (40, 42) with a few modifications. On the day of the assay, 1×10 6 PBMCs were stimulated in vitro with peptide pools (10µg/ml/peptide) at 37°C for additional 6 hrs in a 96-well plate with BD Golgi Stop (BD Biosciences), 10 µl of CD107 a FITC and CD107 b FITC.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of immunogenic peptides of HCV is pivotal for vaccine development, a long-awaited treatment modality. Thus, extensive studies were carried out in the past decade to find immunogenic HCV peptides capable of inducing immune responses (2,9,10,14,(15)(16)(17)(18)(19). As a result, an HCV-derived peptide at positions 35-44 of core protein (C35-44) was determined to be highly immunogenic because of its ability to induce cytotoxic T lymphocytes in HLA-A2-positive HCV-positive patients (2,15,16).…”
Section: Introductionmentioning
confidence: 98%